Tooth surface modification design and contact performance analysis of variable hyperbolic circular-arc-tooth-trace cylindrical gears - MA Dengqiu; JIANG Bing; YE Zhenhuan; DENG Zhenggang (Jixie chuandong)
[Odjective] To improve the bearing capacity of the variable hyperbolic circular-arc-tooth-trace (VH-CATT) cylindrical gear transmission system and reduce the vibration and noise of the system, a tooth surface modification method for the inclined cutter milling was proposed, and the contact performance of the modified VH-CATT cylindrical gear was analyzed.MethodsFirstly, the modified tooth surface equation was derived based on the forming principle, and the tooth surface was reconstructed. Secondly, the influence of different modification parameters on the tooth surface of the modified VH-CATT cylindrical gear was analyzed. Finally, the finite element analysis model of the VH-CATT cylindrical gear was developed, the maximum contact stress and transmission error of the VH-CATT cylindrical gear under different modification parameters were calculated.ResultsThe results show that when the inclination angle of the cutter head increases, the contact stress of the tooth surface decreases, but when it is greater than a certain value γ0, increasing the inclination angle of the cutter head, the VH-CATT cylindrical gear pair produces bridge-type contact, and the contact stress also increases. The influence of modification parameters on the transmission error of the VH-CATT cylindrical gear is consistent with the influence of the tooth surface contact stress. The research results will provide a basis for the high-quality VH-CATT cylindrical gear transmission and gear modification design.